Clinical Control in the Dual Diagnosis of Obstructive Sleep Apnea Syndrome and Rhinitis: A Prospective Analysis. Issue 1 (January 2014) - Parikh, Neil G.; Junaid, Imran; Sheinkopf, Lee; Randhawa, Inderpal; Santiago, Silverio M.; Klaustermeyer, William B.
Background: Obstructive sleep apnea syndrome (OSAS) and allergic rhinitis (AR) are common coexisting disorders. Upper airway, specifically al resistance, is thought to increase during exacerbations of AR and nonallergic rhinitis (NAR), as well as in OSAS. The study objective was to determine if a correlation exists between clinical control of rhinitis and OSAS. Methods: This prospective study followed 43 patients with concurrent OSAS and AR or NAR. OSAS was diagnosed by polysomnography, and AR or NAR was diagnosed by history, skin testing, serum-specific IgE, and total IgE levels. Measurements of control of OSAS included the Epworth Sleepiness Scale (ESS) survey and compliance with continuous positive airway pressure (CPAP) device. Measurements of rhinitis control included Assessment of Nasal Symptom Severity and Assessment of Nonnasal Symptom Severity (NSS refers to both) and Global Assessment of Nasal and Nonnasal Symptom Severity surveys (GSS). Higher NSS scores correlate with more rhinitis symptoms, whereas higher GSS scores correlate with less symptoms. Results: All patients completed the study. There was a positive correlation between ESS and NSS scores (p < 0.001), inverse correlation between ESS and GSS scores (p < 0.001), inverse correlation between CPAP compliance and NSS scores (p < 0.001), and positive correlation between CPAP compliance and GSS scores (p < 0.001). There was no statistically significant difference between the AR, NAR, and AR/NAR groups. Conclusion: Our study showed a statistically significant positive correlation between clinical control of rhinitis symptoms and clinical control of OSAS. This study emphasizes the importance of achieving concurrent optimal control of both OSAS and AR/NAR.